Alocanthedon, a new subgenus of Chalicodoma from Southeast Asia (Hymenoptera, Megachilidae) - Michael Engel (ZooKeys, 2011)
A new subgenus, Alocanthedon Engel and Gonzalez subg. n., is described for five species of unusual Southeast Asian bees in the genus Chalicodoma Lepeletier de Saint Fargeau (Megachilinae: Megachilini). The subgenus is most noteworthy for the deep postgenal depression or furrow in males (bordered outwardly near the base of the mandible by a protuberant, thick lamella) and the presence of a dense patch of black setae posteriorly in the forewing medial cell (except in one species) [resembling the dense patch of setae among the submarginal cells of Thrinchostoma Saussure (Halictidae: Halictinae: Halictini)]. The subgenus is characterized and distinguished from the related Callomegachile Michener. A key to the following five species presently included in the subgenus is provided: Chalicodoma aterrimum (Smith), C. atratiforme (Meade-Waldo) comb. n., C. memecylonae Engel sp. n., C. odontophorum Engel sp. n., and C. apoicola Engel sp. n. Chalicodoma (Callomegachile) atratiforme sininsulae (Cockerell) is newly placed in synonymy with C. (C.) fulvipenne (Smith). Species have been collected from Memecylaceae (Myrtales) and Fabaceae (Fabales). The phylogenetic relationships of Alocanthedon among other Megachilini are briefly elaborated upon.